(untitled) (Annals of Medical Research, 2021)
Aim: Breast cancer is the most common type of cancer in women. The presence and number of metastatic lymph nodes in the axilla are the most significant prognostic factors in breast cancer. In addition, tumor size, lymphovascular invasion, perineural invasion, histopathological type and grade of the tumor are among the best-known prognostic factors. Ki-67 is expressed in G1, S, G2 and M phases of the cell cycle but not in the G0 phase, which allows it to be used as a marker for proliferating cells. The purpose of this study is to determine the relationship between Ki-67 Index and classical prognostic factors in breast cancer patients and to investigate its effect on axillary lymph node metastasis.Material and Methods: 46 patients, who were diagnosed as breast carcinoma in Sivas Cumhuriyet University Medical Faculty Surgical Oncology Department and who underwent a modified radical mastectomy and axillary lymph node dissection between 2017 and 2019 were included in this study. Histological tumor type, stage, status of axillary lymph nodes and Ki-67 Index were evaluated retrospectively from the pathology reports of the patients. The patients were grouped under three categories according to Ki-67 Index. Results: Regarding the grouping of the patients according to Ki-67 Index, the ones below 15% formed the first group, between 15-29% the second group, and above 30% the third group. The distribution of the patients according to negativity-positivity of axillary lymph node metastasis in the groups was as fallow: First group, 7 (41.2%) negative - 10 (58.8%) positive; Second group 4 (33.3%) negative - 8 (66.7%) positive; Third Group 3 (17.6%) negative - 14 (82.4%) positive. Of the 46 patients included in the study, 14 (30.4%) were negative for axillary lymph node metastasis and 32 (69.9%) were positive. In our study, the relationship between the increase of Ki-67 Index and axillary lymph node positivity was found to be statistically significant.Conclusion: In this study, we investigated the relationship between Ki-67 Index and classical prognostic markers, especially lymph node metastasis. Proliferation is an important indicator used to predict prognosis and treatment response in breast cancer. In our study, Ki-67 Index, one of the cell proliferation markers, was found to be positively correlated with axillary lymph node metastasis and other prognostic factors. Therefore, Ki-67 Index was shown to be a significant prognostic indicator in breast cancer.